Strategies to Achieve Student Competence in the Culinary Skills Program in Facing Laboratory Facility Limitations - Fauzia Salmi; Yuliana Yuliana; Jonni Mardizal; Kasmita Kasmita (STKIP Singkawang, 2025)
The success of vocational education in culinary expertise relies heavily on the availability of adequate practical facilities, particularly laboratory infrastructure. However, SMKN 3 Kota Solok faces significant limitations in this area, which hinder students’ ability to achieve optimal competency. This study aims to formulate strategies for enhancing student competency in the culinary program despite laboratory constraints. Using a qualitative descriptive method and SWOT analysis, data were collected through interviews, observations, and documentation. The findings indicate that while internal strengths include committed educators and supportive curricula, weaknesses such as limited space and tools reduce practical learning effectiveness. External opportunities, such as industry collaboration and digital learning platforms, offer pathways for improvement, whereas threats include low graduate absorption in the culinary sector. Strategies developed include optimizing practice rotation, strengthening project-based learning, and increasing industry partnerships. The research concludes that strategic adaptation can significantly improve student competency outcomes even amid facility limitations